Performance of Zero-Till Drill for Lentil Cultivation at Farmer's Fields - Singh, R D; Singh, P M (Journal of Agricultural Engineering, 2006)
Feasibility testing and field evaluation of Pantnagar zero-till drill was conducted at farmers fields during the years (2001-2003). The results of the study were analysed statistically and found that there were significant difference in yield between three treatments with highest yield of 12.65 q/ha (zero till drill), followed by 9.5 q/ha (reduced tillage) and minimum 7.54 q/ha (conventional method). The yield difference of 5.11 q/ha was found between zero till drill and conventional method of seeding. The output to input ratio of 4.45, 2.44 and 1.52 was recorded in zero till drill, reduced tillage and conventional method respectively. The saving in input cost was recorded as Rs. 3174/ha between zero till and conventional method of seeding.